Cooperative control between AtRGS1 and AtHXK1 in a WD40-repeat protein pathway in Arabidopsis thaliana - Huang, Jian-Ping; Tunc-Ozdemir, Meral; Chang, Ying; Jones, Alan M. (Frontiers in Plant Science, 2015)
HEXOKINASE 1 (AtHXK1) and Regulator of G-protein Signaling 1 (AtRGS1) pathways, mediate D-glucose signaling in Arabidopsis. However, it is not known the degree, if any, that these pathways overlap and how. We show modest signaling crosstalk between these pathways, albeit complex with both epistatic interactions and additive effects that may be indirect. The action of HXK1 on AtRGS1 signaling lies downstream of the primary step in G protein-mediated sugar signaling in which the WD-repeat protein, AGB1, is the propelling signaling element. RHIP1, a previously-unknown protein predicted here to have a 3-stranded helical structure, interacts with both AtRGS1 and AtHXK1 in planta and is required for some glucose-regulated gene expression, providing a physical connection between these two proteins in sugar signaling. The rhip1 null mutant displays similar seedling growth phenotypes as rgs1-2 in response to glucose, further suggesting a role for RHIP1 in glucose signaling. In conclusion, glucose signaling is a complex hierarchical relationship which is specific to the target gene and sugar phenotype and suggests that there are two glycolysis-independent glucose signaling sensors: AtRGS1 and AtHXK1 that weakly communicate with each other via feed-back and feed-forward loops to fine tune the response to glucose.